2016
DOI: 10.1002/mus.25251
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the 6 minute walk test in facioscapulohumeral muscular dystrophy

Abstract: Introduction In preparation for future clinical trials, we determined the reliability, relationship to measures of disease severity, and consistency across sites of the 6 minute walk test (6MWT) in patients with facioscapulohumeral muscular dystrophy (FSHD). Methods Genetically defined and clinically affected FSHD participants at 2 sites performed the 6MWT, the Timed Up and Go, and the 30 foot Go/Timed 10 meter test as measures of mobility using standard procedures. Results Eight-six participants represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 34 publications
1
36
1
Order By: Relevance
“…The 6MWT is a well-established measurement of endurance, widely adopted to monitor patients with neuromuscular or cardiorespiratory diseases. It has been validated in many neuromuscular diseases (e.g., Pompe disease, FSHD, Duchenne and Becker dystrophy, spinal muscular atrophy, DM1) but not yet in myotonic dystrophy type 2 (7,(31)(32)(33)(34). In our study the mean distance walked on 6MWT was higher than what reported in previous studies on DM1, this might be surprising considering the more proximal involvement of DM2 but is well-explained by the usually milder phenotype (8).…”
Section: Discussioncontrasting
confidence: 79%
“…The 6MWT is a well-established measurement of endurance, widely adopted to monitor patients with neuromuscular or cardiorespiratory diseases. It has been validated in many neuromuscular diseases (e.g., Pompe disease, FSHD, Duchenne and Becker dystrophy, spinal muscular atrophy, DM1) but not yet in myotonic dystrophy type 2 (7,(31)(32)(33)(34). In our study the mean distance walked on 6MWT was higher than what reported in previous studies on DM1, this might be surprising considering the more proximal involvement of DM2 but is well-explained by the usually milder phenotype (8).…”
Section: Discussioncontrasting
confidence: 79%
“…Manual muscle testing was performed by using a modified Medical Research Council scale (bilateral hip flexors, knee flexors/extensors, and ankle dorsiflexors) . The 6MWT was performed by using a standardized protocol on a linear course . Electrical impedance myography recordings of the bilateral vastus lateralis (VL), tibialis anterior (TA), and medial gastrocnemius (MG) muscles were obtained by using a device from Skulpt (Brookline, Massachusetts) with handheld sensors (20–00045) in longitudinal configuration.…”
Section: Methodsmentioning
confidence: 99%
“…These assessments are detailed below and in Table 1. (8)(9)(10)(11)(12)(13)(14)(15)(16)(32)(33)(34)(35)(36)(37)(38)(39)…”
Section: Assessmentsmentioning
confidence: 99%
“…PHILLIPS ET AL. (8) • Originally developed for assessment of aerobic activity in patients with respiratory disease (9) ; also validated in numerous other patient populations, (10)(11)(12) including those with musculoskeletal diseases (eg, Duchenne/Becker muscular dystrophy, (13,14) facioscapulohumeral muscular dystrophy, (15) spinal muscle atrophy (16) ). • Patients were instructed to walk a 60-m lap along the length of a hallway for 6 min, and the total number of meters walked was recorded.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation